ON τ-BOUNDED SPACES - Karimov Sardor Yashinovich (Journals Park Publishing, 2024)
In this article, it has been proven that τ-bounded spaces, if they satisfy the T2 (Hausdorff space) condition, are also T3 (Regular space) but not necessarily T4 (Normal space), with a counterexample provided. Additionally, the relationship between local weak density and local density has been examined.
Keywords: τ-bounded space, T2 (Hausdorff space), T3 (Regular space), T4 (Normal space), local weak density, local density.